The Historical Origins of an Industrial Disaster: Occupational Health and Labour Relations at the Fluorspar Mines, St. Lawrence, Newfoundland, 1933-1945 - Rennie, Richard (Labour/Le Travailleur, 2005)
Abstract Using union, government, and company records, as well as oral interviews, this article explores the origins of one of the most notorious industrial disasters in Canadian history — the deaths from industrial disease of some 200 fluorspar miners on the south coast of Newfoundland. It explores the social, economic, and political forces that shaped the hazards they believed were destroying their health, and the response of industry and the state to those efforts. Central to the account is a series of strikes that took place during 1941 and the actions of a government tribunal appointed to settle the dispute. Setting events at St. Lawrence in the context of some of the theoretical and methodological considerations intrinsic to the study of occupational health as a labour relations issue, this article not only adds to our knowledge of the forces that shaped this particular disaster, but also represents a contribution to a neglected area of Canadian labour and working-class history.